2014
DOI: 10.2478/cass-2014-0003
|View full text |Cite
|
Sign up to set email alerts
|

Social norms and cultural services - community belief system and use of wildlife products in the Northern periphery of the Korup National Park, South-West Cameroon

Abstract: In many traditional societies, beliefs and taboos influence human behaviour towards the natural environment. Such beliefs and taboos are informal institutions where norms rather than official laws determine land use and nature protection in general and wildlife in particular. The present study on beliefs and taboos of the people of the northern periphery of the Korup National Park is an attempt to reveal how norms influence their relation to the environment. A total of 195 households were sampled through a hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 8 publications
3
6
0
Order By: Relevance
“…At our survey market, many traders have private storerooms and freezers for meat (Randolph, 2016), and in the past other protected species such as gorillas and elephants were available as smoked meat at the same market (Bahuchet & Ioveva, 1999). Our results may also reflect a decline in wild giant pangolins (Nixon et al, 2019), which has been reported in some parts of Cameroon (Abugiche, 2008; Laurent, 1992; Mouté, 2010; Ngoufo et al, 2014).…”
Section: Discussionsupporting
confidence: 70%
“…At our survey market, many traders have private storerooms and freezers for meat (Randolph, 2016), and in the past other protected species such as gorillas and elephants were available as smoked meat at the same market (Bahuchet & Ioveva, 1999). Our results may also reflect a decline in wild giant pangolins (Nixon et al, 2019), which has been reported in some parts of Cameroon (Abugiche, 2008; Laurent, 1992; Mouté, 2010; Ngoufo et al, 2014).…”
Section: Discussionsupporting
confidence: 70%
“…None of these threats are picked up by remote sensing tools. Threats such as hunting primarily affect large-and medium-sized mammals (Benítez-López et al, 2019;Gallego-Zamorano et al, 2020), although regional variations exist because of hunters' preferences, cultural beliefs, and taboos regarding the consumption of some species (Ngoufo et al, 2014;Bobo et al, 2015). For instance, in Uganda ungulates but not primates are targeted by hunters, unlike just over the border in the Democratic Republic of Congo where primates are widely hunted as well (A. Plumptre pers.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we used a binomial model to predict whether mammal populations were locally extinct or not (i.e., whether the relative abundance values were 0 or >0) and then fitted a Gaussian model through the nonzero RRs. We specified as random effects Country, Study, and Species to account for between-country variation in hunting laws and policies, culture, taboos, and traditions [56, 57] and to control for nonindependence in the data from the same study or species. All continuous variables included as fixed effects (see Predictors section) were standardized before model selection, and predictions were done with the models refit with unstandardized predictors.…”
Section: Methodsmentioning
confidence: 99%